Infrasonority: exploration of sound energy below 20Hz in music - Schoeman, Franco (My University, 2017)
This thesis investigates an underdeveloped and little explored area of music and the arts: the use of infrasound (frequencies below 20Hz) as musical material in creative composition. Discussions, research and experiments conducted toward the prospect of exposing infrasonic characteristics were fundamental to the composition and recital that informed the thesis. The infrasonic material from which the composition was created contained synthesized wave forms, recordings of elephant vocalisation and thunderstorms. The infrasonic reproduction for the concert required explicit attention and enquiry regarding physical properties of the sonic phenomenon, equipment infrastructure and limitations in human perception.
A Thesis submitted to the Faculty of Humanities in fulfilment of the requirements for the degree of Master of Music (MMus in Composition), 2017
Keywords: Music; Sound; Music--Acoustics and physics